Analysis of Business Planning in SAF Premier’s Business Development Efforts - Sultan Alif Fajar Hidayatullah; Rr. Ayu Firdausiah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to develop a business development plan and design strategic steps for SAF Premier to strengthen competitiveness and support long-term growth in the furniture industry. Design/Methodology/Approach – This study employs a descriptive qualitative research method. Data were collected through interviews and observations to analyze the current business conditions and formulate appropriate development strategies. Findings – The results indicate that SAF Premier has formulated strategic steps based on an in-depth analysis of its current business conditions. The proposed strategies include more intensive use of social media, development of innovative multifunctional furniture products, optimization of digital marketing to reach broader markets, increased promotional activities, product development, and improvement of customer service quality. Originality/Value This study provides a practical business planning framework tailored to a developing furniture enterprise, integrating strategic analysis to guide long-term competitiveness. The findings offer context-specific insights for enhancing product innovation, digital marketing, and service quality in the modern furniture industry.